Prospective analysis of mid-facial fractures in a single-center pediatric-adolescent cohort. (April 2019) - Reich, Waldemar; Aust, Oliver; Eckert, Alexander
Abstract: Background: The complex architecture of the midface renders diagnosing and treating fractures challenging, especially for young patients who present the additional risk of suffering growth and development deficiencies, which is to be avoided at all costs. Objectives: This study sought to characterize pediatric mid-facial fractures considering the possible complications. Methods: Between September 2008 and September 2018, data was collected on inpatients aged <18 years, treated for mid-facial fractures at the Halle University Hospital. Evaluated parameters were age, gender, cause and type of fracture, associated injuries, treatment, and complications. Results: In total, 31 patients were examined; 20 were boys. The most common cause of injury was road traffic accident (41.9%). Orbital floor fracture was the most common type of injury (58.1%). In 54.8% of cases, surgery was performed. Conclusion: The incidence of complications associated with mid-facial fractures was low (n = 7), requiring treatment in only three cases (orthodontic, ophthalmological).